Men Who Pay for Sex and the Sex Work Movement? Client Responses to Stigma and Increased Regulation of Commercial Sex Policy. Issue 1 (8th September 2014) - Hammond, Natalie
Abstract : Recent years have seen an increase in sex worker organisation, with sex workers and their allies forming unions and collectives, protesting in defence of sex workers' rights, contesting working conditions, opposing criminalisation and aiming to decrease the stigma associated with sex work. However, the actions of male clients have remained invisible. Drawing on empirical data collected from interviews with thirty-five men who pay for sex, and borrowing from social movement literature, specifically Diani's (1992) framework of social movements, this article examines the role of collective identity and the way some clients negotiate political and media constructions of the client figure, and respond to policy processes surrounding the regulation of commercial sex. By taking a cultural studies approach to the sex industry, the article locates commercial sex and its actors within the wider social, cultural and political landscape, reflecting how wider trends regarding the mobilisation and resistance of marginalised groups are apparent within the most unlikely communities.